2020
DOI: 10.18632/aging.103308
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 2 contributes to the effect of salidroside on dendritic and synaptic plasticity after cerebral ischemia/reperfusion injury

Abstract: Ischemic stroke, a serious neurological disease, is associated with cell death, axonal and dendritic plasticity, and other activities. Anti-inflammatory, anti-apoptotic, promote dendritic and synaptic plasticity are critical therapeutic targets after ischemic stroke. Fibroblast growth factor-2 (FGF2), which is involved in the cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA)/CAMP response element (CRE)-binding protein (CREB) pathway, has been shown to facilitate dendritic and synaptic plasticity. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 53 publications
(44 reference statements)
0
35
0
Order By: Relevance
“…In contrast, the microglia M2 phenotype promotes the secretion of anti-inflammatory cytokines, such as IL-4 and IL-10, thus alleviating neuroinflammation and improving neuronal survival (Schmieder et al, 2012). Li et al reported that the pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 in the brain tissue were significantly elevated in the rats with ischemic stroke (Li S. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the microglia M2 phenotype promotes the secretion of anti-inflammatory cytokines, such as IL-4 and IL-10, thus alleviating neuroinflammation and improving neuronal survival (Schmieder et al, 2012). Li et al reported that the pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 in the brain tissue were significantly elevated in the rats with ischemic stroke (Li S. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Salidroside exhibited neuroprotective effects against hypoxia/reperfusion injury by activating the SIRT1/FOXO3α pathway ( Xu, L. et al, 2018 ). In addition, salidroside is an effective treatment for ischemic stroke that functions via the fibroblast growth factor 2 (FGF2)-mediated cAMP/PKA/CREB pathway to promote dendritic and synaptic plasticity ( Li et al, 2020b ). Salidroside treatment reduced the expression of M1 microglia/macrophage markers and increased the exdslbpression of M2 microglia/macrophage markers after stroke and induced primary microglia from M1 phenotype to M2 phenotype ( Liu et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al has demonstrated that FGF2 possess neuroprotective effects through PI3K/Akt activation in a rodent stroke model Zhao et al (2016). A recent study on the mechanism underlying the effects of cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) on ischemic injury depends on regulating apoptosis and inflammation, and FGF2-mediated cAMP/PKA/cAMPresponse element binding protein (CREB) pathway to promote dendritic and synaptic plasticity (Li et al, 2020).…”
Section: Fgf2 In Strokementioning
confidence: 99%